2021
DOI: 10.1002/anie.202108242
|View full text |Cite
|
Sign up to set email alerts
|

Double Proton Transfer Across a Table: The Formic Acid Dimer–Fluorobenzene Complex

Abstract: Proton transfer via tunneling is a fundamental quantum-mechanical phenomenon. We report rotational spectroscopy measurements of this process in the complex of the formic acid dimer with fluorobenzene. The assignment of the spectrum indicates that this complex exists in the form of a p-p stacked structure. Each rotational transition of the parent isotopologue exhibits splitting. Isotopic substitution experiments show that the spectral splitting results from doubleproton transfer tunneling in the formic acid dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…At first slight, the E HB , and E HB Eff and the resulting Δ E 01 values obtained depend strongly on the functionals used, and the precision of the theoretical results appear to be too low to reproduce the experimental data. Similar variations in the theoretical results of proton transfer were reported for the dimers of formic acid and maloic acid, formic acid dimer with fluorobenzene, and also in the large amplitude motion of thiophenol dimers [14,43,45] . Generally, while some usual trend could be predicted, the extremely accurate results provided by rotational spectroscopy are very difficult to reproduce computationally.…”
Section: Resultssupporting
confidence: 65%
See 3 more Smart Citations
“…At first slight, the E HB , and E HB Eff and the resulting Δ E 01 values obtained depend strongly on the functionals used, and the precision of the theoretical results appear to be too low to reproduce the experimental data. Similar variations in the theoretical results of proton transfer were reported for the dimers of formic acid and maloic acid, formic acid dimer with fluorobenzene, and also in the large amplitude motion of thiophenol dimers [14,43,45] . Generally, while some usual trend could be predicted, the extremely accurate results provided by rotational spectroscopy are very difficult to reproduce computationally.…”
Section: Resultssupporting
confidence: 65%
“…The proton transfer dynamics was then calculated using the publicly available Python code [27] . This procedure was used recently for a complex consists of a formic acid dimer and a fluorobenzene molecule [43] . For the reaction coordinate, the following expression was used: trueξ=()rO-H+rO-H-rO···HO-rO···HO/22 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[16] The double proton transfer dynamics in carboxylic acid hetero and homo dimers was extensively characterized by the combination of rotational spectroscopy and the flexible model. [17] Recently, microwave spectroscopy has revealed the influence of neighboring molecules on the proton transfer dynamics of the formic acid dimer, [18] which has been rationalized through solving the one-dimensional Schrödinger equation obtained from a simplistic ab initio computational procedure. [19] In this study, we report the role-exchanging tunneling dynamics observed for a homochiral CD dimer using broad-band chirped-pulse Fourier transform microwave (CP-FTMW) spectroscopy, [20] also known as Molecular Rotational Resonance (MRR) spectroscopy.…”
mentioning
confidence: 99%